Issues of US-EU Trade Policy - Wilhelm Kohler (Johannes Kepler University of Linz, Department of Economics, 2002)
Comment on Trade and Investment: An American Perspective by G. Hufbauer and F. Neumann Old and New Issues in EC-US Trade Disputes by André Sapir
Keywords: 330; Internationale Wirtschaftsbeziehungen; Außenhandelspolitik; EU-Staaten; USA